Phosphorus-carbon-silver composite material and preparation method and application thereof

The preparation of phosphorus-carbon-silver composite material by solvent thermal reaction method solved the problem of cumbersome composite process between black phosphorus and carbon material, achieved an efficient and simple preparation process, and obtained excellent electrochemical properties.

CN119447221AActive Publication Date: 2025-02-14HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411333015.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The composite process of black phosphorus and carbon material of the existing lithium-ion battery negative electrode material is cumbersome and has low production efficiency.

Method used

The phosphorus-carbon-silver composite material was prepared by solvothermal reaction method. By mixing carbon material, silver source, black phosphorus and reducing agent, solvothermal reaction was performed to obtain a composite material with excellent conductivity and electrochemical properties.

Benefits of technology

This method simplifies the preparation process, improves production efficiency, and avoids impurities problems in the ball milling method. The prepared composite material has high purity and excellent electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447221A_ABST
    Figure CN119447221A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus-carbon-silver composite material as well as a preparation method and application thereof, and belongs to the field of lithium ion battery negative electrode materials. The preparation method comprises the following steps: S1, preparing a mixed solution containing a carbon material, a silver source, black phosphorus and a reducing agent; s2, the mixed solution is subjected to a solvothermal reaction, and a phosphorus-carbon-silver composite material is obtained; wherein in the step S2, the temperature of the solvothermal reaction is 60-140 DEG C, and the time is 3-24 hours; the method is simple in preparation step, beneficial to improvement of production efficiency and more suitable for industrialization. And on the other hand, the prepared phosphorus-carbon-silver composite material has excellent electrochemical properties such as conductivity, charge-discharge cycle and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for lithium ion batteries, and more specifically, relates to a phosphorus-carbon-silver composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are one of the most widely used energy storage devices. They have the advantages of high energy density and green environmental protection. In order to further improve the performance of lithium-ion batteries, including service life, fast charging, high and low temperature performance, etc., the optimization of negative electrode materials is very important. Currently, the most commonly used negative electrode material for lithium-ion batteries is graphite. However, the low theoretical capacity of graphite negative electrode (372mAh / g) is difficult to meet the needs of energy development.

[0003] Phosphorus is widely available, and the theoretical lithium storage capacity of elemental phosphorus as a negative electrode material for lithium-ion batteries is as high as 2596 mAh / g, which is much higher than that of graphite negative electrode. It is a research hotspot for negative electrode materials of next-generation lithium-ion batteries. Black phosphorus, as one of the allotropes of phosphorus, has a high lithium ion diffusion efficiency and is an ideal negative electrode material for achieving high energy density and fast charging performance of lithium-ion batteries. However, when black phosphorus is used as a negative electrode material alone, its conductivity is poor, and a large volume change occurs during the charging and discharging process. Composite black phosphorus and carbon materials can improve the problems of poor conductivity and volume expansion. At present, most of the methods for composite black phosphorus with carbon materials are ball milling, and the steps are relatively complicated and cumbersome. For example, a Chinese patent with publication number CN115172711A discloses a black phosphorus-carbon composite material and its preparation method and application, but in the patent, the method for composite black phosphorus with carbon materials is: amorphous red phosphorus and conductive carbon material are ball milled under a protective atmosphere, and pressed and formed, and reacted at high temperature and high pressure to obtain a black phosphorus-carbon composite material. This process is relatively cumbersome and has low production efficiency.

[0004] Therefore, a method for preparing a composite material of black phosphorus and carbon material with simple operation is needed. Summary of the invention

[0005] 1. Problem to be solved

[0006] In view of the problem that the composite process of black phosphorus and carbon materials in the prior art of lithium-ion battery negative electrode materials is complicated, a phosphorus-carbon-silver composite material and a preparation method thereof are provided; a phosphorus-carbon-silver composite material with excellent electrical conductivity, charge-discharge cycle and rate performance is also provided.

[0007] 2. Technical solution

[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a method for preparing a phosphorus-carbon-silver composite material:

[0010] S1. Preparing a mixed solution containing a carbon material, a silver source, black phosphorus, and a reducing agent;

[0011] S2. subjecting the mixed solution to a solvothermal reaction to obtain a phosphorus-carbon-silver composite material.

[0012] It should be noted that in the prior art, the phosphorus-carbon composite process of the negative electrode material of lithium-ion batteries mainly adopts the ball milling method, which is cumbersome to operate and the weight and volume of the ball mill equipment used are large; the preparation method described in the present invention can obtain a phosphorus-carbon-silver composite material with higher purity, and the preparation steps of the composite material are simple, which can not only improve the production efficiency, but also do not need to use heavy equipment such as ball mills, and are more suitable for industrialization;

[0013] On the other hand, ball milling is a physical mixing method, which is easy to introduce dust and impurities caused by the wear of the grinding balls. The preparation method described in the present invention avoids this problem, and the purity of the mixed liquid is higher, which is conducive to ensuring the quality and electrochemical properties of the prepared phosphorus-carbon-silver composite material.

[0014] Further, in step S2, the temperature of the solvent thermal reaction is 60 to 140° C., and the time is 3 to 24 hours;

[0015] The temperature may specifically be 60-140°C, 70-140°C, 80-140°C, 90-140°C, 100-140°C, 110-140°C, 120-140°C, 130-140°C;

[0016] The specific time can be 3-4h, 3-6h, 3-8h, 3-10h, 3-12h, 3-14h, 3-16h, 3-18h, 3-20h, or 3-24h.

[0017] It should be noted that controlling the temperature and time of the solvent thermal reaction within the above range is conducive to the uniform modification of Ag nanoparticles to the surface of the material to improve the conductivity of the phosphorus-carbon-silver composite material, and is also conducive to the formation of a cross-linked structure between the carbon material and black phosphorus to inhibit the volume expansion of black phosphorus during the cycle, thereby preparing a phosphorus-carbon-silver composite material with excellent electrochemical properties.

[0018] If the reaction temperature is lower than 60°C, the reaction effect may be poor, affecting the performance of the prepared composite material; if the reaction temperature is higher than 140°C, the rapid evaporation of the solvent may accelerate the volatilization of the reducing agent, resulting in a reduction of the reducing agent in the reaction system, affecting the uniformity of the reaction; in addition, some reactants or solvents may decompose at a temperature exceeding their thermal stability, producing by-products, affecting the purity of the material, and may even cause damage to the material structure.

[0019] Preferably, in step S2, the reaction temperature of the solvent thermal reaction is 100-140° C., and the reaction time is 3-10 h.

[0020] It should be noted that in the prior art, the ball milling method mainly used in the phosphorus-carbon composite process of lithium-ion battery negative electrode materials is cumbersome to operate, requires 12 to 24 hours of ball milling time, and has low efficiency;

[0021] The composite material in the preparation method only takes less than 10 hours to compound, which greatly improves the production efficiency and is conducive to industrialization.

[0022] Furthermore, in step S1, the mass ratio of silver to black phosphorus in the silver source is 1:10 to 1:1.

[0023] Furthermore, in step S1, the mass ratio of the carbon material to black phosphorus is 1:10 to 1:1.

[0024] Furthermore, in step S1, the mass ratio of the reducing agent to black phosphorus is 10:1 to 100:1.

[0025] It should be noted that controlling the mass ratios of the silver source and black phosphorus, the carbon material and black phosphorus, and the reducing agent and black phosphorus within the above range is beneficial to controlling the Ag nanoparticles generated by the reduction of silver ions and uniformly modifying them on the surface of the carbon material to improve conductivity. It is also beneficial to the formation of a cross-linked structure between the carbon material and black phosphorus to inhibit the volume expansion and volume change of black phosphorus during the cycle. The prepared phosphorus-carbon-silver composite material has excellent electrochemical properties of electrical conductivity, charge and discharge cycle and rate performance.

[0026] Furthermore, in step S1, the carbon material includes one, two or more of carbon nanotubes, carbon black and graphite powder.

[0027] Furthermore, in step S1, the silver source includes one or both of silver nitrate and silver fluoride.

[0028] Furthermore, the silver source is added in the form of a silver nitrate aqueous solution, a silver ammonia solution or a silver fluoride aqueous solution.

[0029] It should be noted that the silver source has a good dissolution effect in the above solution. Adding it in the form of the above solution can improve the dispersibility of the silver source in the mixed solution, so that the silver ions can be fully reduced and the distribution of the Ag nanoparticles obtained by reduction can be more uniform.

[0030] Furthermore, the molar concentration of silver in the silver nitrate aqueous solution, silver ammonia solution or silver fluoride aqueous solution is 0.01-0.1 mol / L.

[0031] It should be noted that controlling the molar concentration of silver in the silver nitrate aqueous solution, silver ammonia solution or silver fluoride aqueous solution within the above range is beneficial to reducing silver ions to Ag nanoparticles under the temperature and conditions of the above-mentioned solvent thermal reaction and reducing the occurrence of side reactions.

[0032] Preferably, the silver nitrate aqueous solution is freshly prepared and used.

[0033] Furthermore, in step S1, the reducing agent includes one or both of N,N-dimethylformamide (DMF) and sodium borohydride.

[0034] It should be noted that DMF has good solubility and affinity for a variety of substances. It can mix carbon materials, silver sources and black phosphorus to form a uniform slurry to avoid agglomeration; it can also promote the reduction of metallic silver ions through reduction reactions, acting as a reducing agent; and it forms a good interaction with carbon materials, etc., which is conducive to the preparation of phosphorus-carbon-silver composite materials with excellent electrochemical properties such as conductivity and cycle performance.

[0035] For example, when the reducing agent is sodium borohydride, the silver source can be added in the form of an aqueous silver nitrate solution, an ammoniacal silver solution, or an aqueous silver fluoride solution.

[0036] Furthermore, in step S1, the black phosphorus includes one, two or more of black phosphorus nanosheets, black phosphorus quantum dots and black phosphorus powder.

[0037] It should be noted that the above-mentioned black phosphorus material can form a cross-linked structure with the above-mentioned carbon material. Black phosphorus has a higher theoretical specific capacity and can provide more charge storage sites. It has a certain electronic conductivity, which helps to improve the electrical conductivity of the composite material and reduce the resistance during battery charging and discharging.

[0038] Furthermore, step S1 also includes adjusting the pH value of the mixed solution to 5.4-6.4.

[0039] It should be noted that adjusting the pH value to 5.4-6.4 is beneficial to improving the dispersibility of the carbon material in the reducing agent, such as DMF, maintaining the stability of the carbon material, and promoting the interaction and combination of the carbon material with silver nanoparticles and black phosphorus, so as to enhance the conductivity and charge-discharge cycle and rate performance of the phosphorus-carbon-silver composite material.

[0040] Furthermore, nitric acid may be used to adjust the pH value to 5.4-6.4.

[0041] For example, the pH value can be adjusted to 5.4 to 6.4 after the mixed solution is prepared.

[0042] Preferably, in step S1, the carbon material is carbon nanotubes, the silver source is silver nitrate, the black phosphorus is black phosphorus nanosheets, and the reducing agent is DMF.

[0043] It should be noted that based on the reduction reaction of silver nitrate and DMF (reducing agent), Ag nanoparticles are uniformly modified on the CNT surface, which can improve the conductivity of the composite material. The addition of CNT can fix the cross-linked black phosphorus nanosheets, construct a phosphorus-carbon composite structure, that is, form a cross-linked structure, inhibit the volume expansion and volume change of black phosphorus during the cycle, and improve the charge and discharge cycle and rate performance of the composite material.

[0044] On the other hand, black phosphorus nanosheets can be compounded with metallic silver to improve the energy density and power density of the battery.

[0045] Furthermore, step S1 is specifically as follows:

[0046] Add the carbon material to the reducing agent and stir evenly, and adjust the pH value to 5.4-6.4;

[0047] Then add the silver source and stir for 30-60 minutes;

[0048] Add black phosphorus and stir until evenly dispersed.

[0049] Furthermore, the stirring may be magnetic stirring.

[0050] Furthermore, in step S2, the solvent thermal reaction further includes post-treatment;

[0051] The post-treatment includes cooling, washing and drying in sequence.

[0052] It should be noted that the cooling process in the post-treatment helps to stabilize the composite material to maintain good performance; the purpose of washing is to remove residues attached to the surface and improve the purity of the material, which is conducive to its subsequent use in preparing battery negative electrodes; the purpose of the drying process is to remove the solvent to prevent residual solvent from affecting the application effect of the material.

[0053] Furthermore, the cooling may be cooling to room temperature;

[0054] The washing may be performed by using ethanol or acetone;

[0055] The drying temperature is 80-150° C. and the drying time is 30-60 minutes.

[0056] The drying may be vacuum drying.

[0057] The present invention also provides a phosphorus-carbon-silver composite material prepared according to the above-mentioned method for preparing the phosphorus-carbon-silver composite material.

[0058] Furthermore, the phosphorus-carbon-silver composite material comprises black phosphorus, carbon material and silver nanoparticles.

[0059] The silver nanoparticles are attached to the surface of the carbon material, and the black phosphorus forms a cross-linked structure with the carbon material.

[0060] It should be noted that, in the phosphorus-carbon-silver composite material, silver nanoparticles are introduced and uniformly attached to the surface of the carbon material, thereby improving the electrical conductivity of the composite material; wherein, "silver nanoparticles are uniformly attached to the surface of the carbon material" means that on the carbon nanotubes, the arrangement of the silver nanoparticles presents a relatively dispersed and uniform particle size state, that is, there is no significant local deviation or aggregation phenomenon in the spacing, density or number distribution between the particles;

[0061] A phosphorus-carbon composite structure was also constructed. The carbon material plays a role in fixing and cross-linking black phosphorus to form a cross-linked structure, which can significantly alleviate the volume change of black phosphorus during the charging and discharging process of the battery.

[0062] Furthermore, the particle size of the silver nanoparticles is 10 to 100 nm.

[0063] It should be noted that the particle size of the silver nanoparticles being within the above range is beneficial for the composite material to have excellent electrical conductivity and is also beneficial for improving the structural stability of the composite material.

[0064] The present invention also provides a negative electrode for a lithium ion battery, wherein the negative electrode comprises the phosphorus-carbon-silver composite material prepared by the above preparation method or the above phosphorus-carbon-silver composite material.

[0065] It should be noted that, due to the phosphorus-carbon-silver composite material, the negative electrode of the lithium-ion battery has excellent electrical conductivity, charge-discharge cycle and rate performance.

[0066] 3. Beneficial effects

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] (1) The phosphorus-carbon-silver composite material provided by the present invention is prepared by a solvothermal method, which has the advantages of mild reaction conditions, simple operation, simple equipment, and easy scale-up compared to the traditional ball milling process.

[0069] (2) The phosphorus-carbon-silver composite material provided by the present invention introduces silver nanoparticles to help improve the conductivity of the composite material, and also constructs a phosphorus-carbon composite structure. The carbon material plays a role in fixing black phosphorus to form a cross-linked structure, which inhibits the volume expansion of black phosphorus during the cycle process, so that it has excellent electrochemical properties of charge and discharge cycle and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 is a TEM image of the Ag-CNT-BP composite material 1 in Example 1 of the present invention;

[0071] Figure 2 is a TEM image of the Ag-CNT-BP composite material 1 in Example 1 of the present invention;

[0072] Figure 3 is the X-ray diffraction pattern of the Ag-CNT-BP composite material 1 in Example 1 of the present invention;

[0073] Figure 4 This is an electrochemical cycle performance diagram of a lithium ion half-cell assembled using the Ag-CNT-BP composite material 1 in Example 1 of the present invention;

[0074] Figure 5 This is an electrochemical rate performance diagram of a lithium ion half-cell assembled using the Ag-CNT-BP composite material 1 in Example 1 of the present invention. DETAILED DESCRIPTION

[0075] It should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0076] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0077] As used herein, the term "one, two, or more of" expressly includes only A, only B, only C, and combinations of each thereof.

[0078] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values ​​or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values ​​and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.

[0079] The present invention is further described below in conjunction with specific embodiments. The following embodiments are only partial embodiments of the present invention, rather than all embodiments. Unless otherwise specified, all equipment and raw materials in the present invention are commercially available products commonly used in the art. Unless otherwise specified, the methods in the embodiments are all conventional methods in the art.

[0080] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0081] In the embodiments of the present invention, CNT is the C301993 product purchased from Aladdin; DMF is the D112004 product purchased from Aladdin; BP nanosheets (black phosphorus nanosheets) are the XF2077723-14-0 product purchased from Xianfeng Nanotechnology.

[0082] Example 1

[0083] This embodiment provides a method for preparing an Ag-CNT-BP composite material, comprising the following steps:

[0084] Add 100 mL of deionized water into a 200 mL beaker, add 1.6987 g of AgNO3 while stirring with a magnetic stirrer, and stir until completely dissolved to obtain a colorless, uniform silver nitrate solution (0.1 mol / L).

[0085] 0.5 g of CNT was added to 260 mL of DMF, and then stirred. The pH value was adjusted to 6.0 with nitric acid (nitric acid, 0.01 mol / L). Then 100 mL of silver nitrate solution (0.1 mol / L) was added, and the whole process was kept stirring. After stirring and dispersing for 30 minutes, 3.5 g of BP nanosheets were added and continued to stir until uniformly dispersed. The uniformly dispersed mixed solution was reacted at 120°C for 12 hours, and after the reaction was completed, it was naturally cooled to room temperature and washed with anhydrous ethanol. The remaining solid was vacuum dried at 80°C for 30 minutes to obtain Ag-CNT-BP composite material 1.

[0086] Example 2

[0087] This embodiment provides a method for preparing an Ag-CNT-BP composite material, comprising the following steps:

[0088] The preparation method of the Ag-CNT-BP composite material in this embodiment is basically the same as that in Embodiment 1, except that the mixed solution is reacted at 80° C. for 6 hours.

[0089] Finally, Ag-CNT-BP composite material 2 was obtained.

[0090] Example 3

[0091] This embodiment provides a method for preparing an Ag-CNT-BP composite material, comprising the following steps:

[0092] The preparation method of the Ag-CNT-BP composite material in this embodiment is basically the same as that in Embodiment 1, except that the mixed solution is reacted at 60° C. for 3 h.

[0093] Finally, Ag-CNT-BP composite material 3 was obtained.

[0094] Comparative Example 1

[0095] This embodiment provides a method for preparing a CNT-BP composite material, comprising the following steps:

[0096] 0.5 g of CNT was added to 260 mL of DMF, and then stirred. After stirring and dispersing for 30 minutes, 3.5 g of BP nanosheets were added and stirred until uniformly dispersed. The uniformly dispersed mixed solution was reacted at 120° C. for 12 hours. After the reaction was completed, it was naturally cooled to room temperature and washed with anhydrous ethanol. The remaining solid was vacuum dried at 80° C. for 30 minutes to obtain a CNT-BP composite material.

[0097] The Ag-CNT-BP composite material 1 prepared in Example 1 was characterized by TEM and XRD. The obtained TEM image is as follows: Figure 1 , Figure 2 As shown in the figure, the black flakes are black phosphorus nanosheets, the granular ones are single-element Ag, and the tubular ones are CNTs. Figure 1 As can be seen from the figure, the elemental silver is in granular form with uniform particle size and is loaded on the surface of CNT. At the same time, CNT plays a cross-linking role on the black phosphorus nanosheets. As can be seen from the figure, the elemental silver is evenly distributed in the material. Figure 3 This is the XRD spectrum of the Ag-BP-CNT composite material 1 of Example 1. From the diffraction peaks in the figure, it can be seen that there are no other impurity peaks in the material except BP, elemental silver and CNT, which proves that the purity of the Ag-CNT-BP composite material 1 is very high.

[0098] The composite materials prepared in the above embodiments and comparative examples were used as active materials. The active materials, conductive carbon black, and polyvinylidene fluoride (PVDF) were evenly ground in a mortar at a mass ratio of 8:1:1, and an appropriate amount of NMP was added and stirred by a homogenizer to obtain a mixed slurry. After coating and rolling with a small coater and a roller press, the mixture was dried at 80°C in a vacuum drying oven for 12 h and sliced ​​with a slicer. The negative electrode sheet was assembled into a lithium ion half-cell in a glove box with a polypropylene (PP) diaphragm, a battery shell CR2032 model button battery shell, metallic lithium, and an electrolyte (1M LiPF6 dissolved in EC:DEC:FEC:VC=1:1:1:1 (volume ratio)). The cycle and rate performance were tested at room temperature. The test results are shown in Table 1.

[0099] Combination Figure 4 When the Ag-CNT-BP composite material 1 of Example 1 is used as the negative electrode material to be assembled into a lithium-ion half-cell, the battery has a first-cycle discharge capacity of 1901.6 mAh / g, a charge capacity of 1433.4 mAh / g, a first-cycle coulomb efficiency of 75.4%, a capacity retention rate of 77.2% after 60 cycles, and a stable coulomb efficiency of 99.2%.

[0100] When the Ag-CNT-BP composite material 1 of Example 1 is used as the negative electrode active material to be assembled into a lithium ion half-cell, the battery has a charge capacity of 1106.9 mAh / g after 60 cycles at a current density of 1.0 A / g, and a capacity retention rate of 77.2%, indicating that it has good cycle performance.

[0101] The CNT-BP composite material in Comparative Example 1 was prepared in the same steps except that no silver nitrate solvent was added to the reaction. However, the discharge specific capacity of the CNT-BP composite material prepared therefrom after 60 cycles at a current density of 1.0 A / g was only 574.3 mAh / g, and the charge specific capacity was only 577.2 mAh / g. It can be seen that Ag nanoparticles effectively improved the electrochemical properties of the phosphorus-carbon-silver composite material.

[0102] In addition, combined Figure 5 When the composite material of Example 1 is used as the negative electrode active material to assemble into a lithium ion half-cell, the battery can be charged and discharged in the range of 0.2 to 4.0 A / g, and the specific capacity at 4.0 A / g reaches 373.6 mAh / g. Therefore, the Ag-CNT-BP composite material has excellent rate performance. This may be due to the good composite between Ag-CNT and black phosphorus, which improves the conductivity of black phosphorus and effectively inhibits the volume expansion of black phosphorus during charging and discharging.

[0103] In addition, the cycle and rate performance of Ag-CNT-BP composite materials 2 and Ag-CNT-BP composite materials 3 in Examples 2 and 3 are lower than those of Ag-CNT-BP composite material 1. This may be due to the reduction in temperature and time of the reduction reaction, which leads to incomplete reaction of silver nitrate and fewer silver nanoparticles attached to the CNTs, resulting in reduced electrochemical performance of the Ag-CNT-BP composite materials.

[0104] Table 1 Performance test of composite materials in embodiments and comparative examples

[0105]

[0106] Note: The test conditions for the above first-cycle discharge specific capacity are: current density: 1.0A / g; test voltage 0.1~2.5V.

[0107] The test conditions for the above first cycle charge specific capacity are: current density: 1.0A / g; test voltage 0.1~2.5V.

[0108] The test conditions of the above cyclic discharge specific capacity are: number of cycles: 60 cycles; current density: 1.0A / g; test voltage 0.1~2.5V.

[0109] The test conditions of the above-mentioned cyclic charging specific capacity are: number of cycles: 60 cycles; current density: 1.0A / g; test voltage 0.1~2.5V.

[0110] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a phosphorus-carbon-silver composite material, characterized in that: S1. Preparing a mixed solution containing a carbon material, a silver source, black phosphorus, and a reducing agent; S2. subjecting the mixed solution to a solvothermal reaction to obtain a phosphorus-carbon-silver composite material; Wherein, in step S2, the temperature of the solvent thermal reaction is 60-140° C., and the time is 3-24 hours.

2. The method for preparing the phosphorus-carbon-silver composite material according to claim 1, characterized in that: In step S1, the mass ratio of the carbon material to black phosphorus is 1:10 to 1:

1.

3. The method for preparing the phosphorus-carbon-silver composite material according to claim 2, characterized in that: In step S1, the mass ratio of silver to black phosphorus in the silver source is 1:10 to 1:1; The mass ratio of the reducing agent to black phosphorus is 10:1 to 100:

1.

4. The method for preparing the phosphorus-carbon-silver composite material according to any one of claims 1 to 3, characterized in that: In step S1, the carbon material includes one, two or more of carbon nanotubes, carbon black and graphite powder; The black phosphorus includes one, two or more of black phosphorus nanosheets, black phosphorus quantum dots and black phosphorus powder.

5. The method for preparing the phosphorus-carbon-silver composite material according to claim 4, characterized in that: In step S1, the silver source includes one or both of silver nitrate and silver fluoride; The reducing agent includes one or both of N,N-dimethylformamide and sodium borohydride.

6. The method for preparing the phosphorus-carbon-silver composite material according to claim 5, characterized in that: Step S1 also includes adjusting the pH value of the mixed solution to 5.4-6.

4.

7. The method for preparing the phosphorus-carbon-silver composite material according to any one of claims 1 to 3, characterized in that: In step S1, the carbon material is carbon nanotubes, the silver source is silver nitrate, the black phosphorus is black phosphorus nanosheets, and the reducing agent is DMF.

8. A phosphorus-carbon-silver composite material prepared by the method for preparing a phosphorus-carbon-silver composite material according to any one of claims 1 to 7, characterized in that: The phosphorus-carbon-silver composite material comprises black phosphorus, carbon material and silver nanoparticles, The silver nanoparticles are attached to the surface of the carbon material, and the black phosphorus forms a cross-linked structure with the carbon material.

9. The phosphorus-carbon-silver composite material according to claim 8, characterized in that: The particle size of the silver nanoparticles is 10-100 nm.

10. A negative electrode for a lithium ion battery, characterized in that: The negative electrode comprises a phosphorus-carbon-silver composite material prepared by the preparation method according to any one of claims 1 to 7, or a phosphorus-carbon-silver composite material according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Black phosphorus-carbon composite material as well as preparation method and application thereof

    CN115172711A

  • Method for anchoring metal nanoparticles to carbon nanotubes

    CA3190641A1

  • Black phosphorus-based negative electrode material and preparation method thereof

    CN113437281A

  • High-safety and high-performance battery negative electrode material

    CN113725425A

  • Silver-loaded graphite carbon nitride nanosheet as well as preparation method and application thereof

    CN115887648A